Analisis Sentimen Review Tempat Wisata Pada Data Online Travel Agency Di Yogyakarta Menggunakan Model Neural Network IndoBERTweet Fine Tuning - Muhammad Zidni Subarkah; Martina Hilda; Etik Zukhronah (Politeknik Statistika STIS, 2022)
Tourism is a leading sector in Indonesia, one of which is D.I. Yogyakarta. In 2017, the total number of tourists visiting DIY was 5,229,298. The high intensity of tourist visits is directly proportional to data on people's preferences for tourist attractions. From this problem, authors are interested in conducting a sentiment analysis of tourist attractions with the IndoBERTweet Fine Tuning Neural Network model using Online Travel Agency (OTA) data. This analysis is intended so that the government and local tourism managers can easily take a decision or policy in increasing the comfort of tourist attractions. Based on this analysis, five tourist attractions with the highest number of visitor reviews were obtained, namely, Malioboro Street, Tamansari Water Palace, Yogyakarta Palace, Yogyakarta Smart Park, and Yogyakarta Monument. Sentiment analysis of this classification produces an accuracy value of 92.84%, with weighted average recall of 93%, precision of 92%, and F1-Score of 93%.